2021
DOI: 10.1186/s12903-021-01793-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of remote digital monitoring on oral hygiene of orthodontic patients: a prospective study

Abstract: Background Remote digital monitoring during orthodontic treatment can help patients in improving their oral hygiene performance and reducing the number of appointments due to emergency reasons, especially in time of COVID-19 pandemic where non-urgent appointments might be discouraged. Methods Thirty patients scheduled to start an orthodontic treatment were divided into two groups of fifteen. Compared to controls, study group patients were provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 36 publications
2
28
1
1
Order By: Relevance
“…15,16 The use of smartphones and digital technology can be useful in evaluating the progression of the treatment and improving the patient's cooperation. 17 Due to the current pandemic, 63% of the patients could not visit their orthodontist for the last 3-6 months. Despite this long period, a good number (63%) of patients regularly followed the instructions given by their orthodontist.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 The use of smartphones and digital technology can be useful in evaluating the progression of the treatment and improving the patient's cooperation. 17 Due to the current pandemic, 63% of the patients could not visit their orthodontist for the last 3-6 months. Despite this long period, a good number (63%) of patients regularly followed the instructions given by their orthodontist.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 20 In the past few years, the market has assisted an increased availability of orthodontic apps to enhance long-distance monitoring and compliance, 21 and a recent study confirmed the positive attitude of patients towards this new digital technology. 22 In orthodontics, it can be applied for monitoring of several treatment aspects, 23 including patients’ oral hygiene during the therapy, 16 , 24 , 25 treatment with clear aligners, 26 , 27 rapid palatal expansion, 15 , 28 , 29 adherence to the use of removable retainers, 8 active working time of self-ligating straight-wire appliances, 30 and clinical follow-up of corticotomy-accelerated orthodontic therapies. 31 …”
Section: Discussionmentioning
confidence: 99%
“…This problem was not reported in studies in which this technology was applied on a weekly basis. 16 This may suggest that the monthly frequency of scanning leads the patient to forget the method of capturing accurate pictures compared to more frequent monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those who reported declined cooperation expected that the lockdown would have a detrimental impact on the treatment quality and duration. Sangalli et al [ 31 ] showed that remote monitoring during orthodontic treatment improves patients’ plaque control and reduces the onset of carious lesions. Thus, continuous follow ups and remote support may play an important role in improving patients’ cooperation and subsequently, may influence their attitudes regarding treatment success.…”
Section: Discussionmentioning
confidence: 99%